Kontribusi Pendidikan Vokasi terhadap Pemberdayaan Perempuan dalam Pertumbuhan Ekonomi melalui Sektor Formal: Sitematis Literatur Review - Isnaini, Lina; Sabandi, M.; Wardani , Kusuma Dewi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This paper aims to analyze the contribution of vocational education to women's empowerment and its impact on economic growth through the formal sector in Indonesia. Employment opportunities for women are very low and have led to increased unemployment for women and a significant gender wage gap, as women are more likely to work in the informal sector, limiting their access to non-financial benefits such as health insurance and paid maternity leave. Using a Systematic Literature Review (SLR) method on 26 international and national scientific articles, this study highlights the role of vocational education, particularly Vocational Training Centers (BLK), in improving skills, social inclusion, and gender equality in the labor market. The review results show that government investment in vocational education is positively correlated with formal economic growth by increasing labor productivity and strengthening women's capacity in the modern economic sector. Gender-responsive TVET programs have been shown to improve women's employability, economic independence, and participation in household and public decision-making. However, structural barriers such as patriarchy, gender stereotypes, and limited access to capital remain major challenges. Therefore, affirmative policies, institutional support, and synergy between government, industry, and training institutions are needed so that TVET truly becomes a transformative instrument in strengthening gender equality and supporting the achievement of Sustainable Development Goal (SDGs) 5. Thus, vocational education is not only a tool to improve workforce skills, but also a driving force for inclusive and sustainable economic development.